Cronkhite-Canada Syndrome: Gastric Involvement Diagnosed by MDCT - Jonathan D. Samet; Karen M. Horton; Elliot K. Fishman; Christine A. Iacobuzio-Donahue (Case Reports in Medicine)
Chronkhite-Canada is a rare nonfamilial polyposis syndrome that usually presents as chronic malabsorption in adults. We present a case of a-73-year old woman with chronic gastrointestinal bleeding and malnutrition. On CT imaging she was found to have massive gastric polyps, which on biopsy was most consistent with Cronkhite-Canada syndrome.